A venom protein of ectoparasitoid Pachycrepoideus vindemiae, PvG6PDH, contributes to parasitism by inhibiting host glucose‐6‐phosphate metabolism. (1st November 2021) - Yang, Lei; Qiu, Liming; Fang, Qi; Wu, Shaoying; Ye, Gongyin
Abstract: To achieve successful development, female parasitoids, while laying eggs, introduce various virulence factors, mainly venoms, into host insects to manipulate their physiology. Although numerous studies have been conducted to characterize the components of venoms that regulate host immune responses, few systematic investigations have been conducted on the roles of venom proteins in host metabolic regulation. In this investigation, we characterized a novel venom protein in Pachycrepoideus vindemiae called glucose‐6‐phosphate dehydrogenase (PvG6PDH) and showed it has a vital role in regulating host carbohydrate metabolism. PvG6PDH encodes 510 amino acids and features a signal peptide and two conserved "G6PDH" domains. Multiple sequence alignment showed it has high amino acid identity with G6PDH from other pteromalids, and quantitative polymerase chain reaction analysis and immunofluorescent staining demonstrated a significantly higher expression of PvG6PDH in the venom apparatus compared with the carcass. We report that PvG6PDH contributes to parasitism by inhibiting the glucose‐6‐phosphate (G6P) metabolism of host Drosophila melanogaster, as demonstrated by PvG6PDH injection and RNA interference analysis. Further tests revealed that the accumulation of host G6P was caused by the transcriptional inhibition of G6P‐metabolism‐related genes. These findings greatly contribute to our understanding of venom‐mediated host metabolic regulation, further laying the foundation for the development of venom proteins as biological agents for pest control. Abstract : We identified a novel venom protein from Pachycrepoideus vindemiae, PvG6PDH, which contributed to parasitism by inhibiting the G6P metabolism of host Drosophila melanogaster .